2002
DOI: 10.1007/bf02835544
|View full text |Cite
|
Sign up to set email alerts
|

Organic synthesis under solvent-free condition: An environmentally benign procedure — I

Abstract: His main area of research is organosilicon chemistry with particular attention to developing new synthetic procedures and reagents, and studying the reaction mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 4 publications
0
32
0
Order By: Relevance
“…[6][7][8] On the other hand, these catalysts or reagents could be used under heterogeneous solvent-free conditions for conducting more environmentally benign reactions. 9 These methods have simple work-up and diminished pollutant materials and also energy consumptions in comparison with conventional work-up of solution-phase reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] On the other hand, these catalysts or reagents could be used under heterogeneous solvent-free conditions for conducting more environmentally benign reactions. 9 These methods have simple work-up and diminished pollutant materials and also energy consumptions in comparison with conventional work-up of solution-phase reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, grindstone chemistry has been shown to be a highly viable green and rapid method for the synthesis of organic compounds without the complicacies associated with the use of different solvents, including water [4]. The proposed technique does not require external heating, leading to energy efficient synthesis and may be regarded as more economical and ecologically favorable procedure in chemistry [5]. Toda and coworkers showed that many of the exothermic organic reactions can be performed in good yield using mortar and pestle only [4].…”
Section: Introductionmentioning
confidence: 99%
“…An important area of green chemistry deals with solvent minimization. A solvent-free or solid-state reaction may be carried out by using the reactants alone or incorporating them in clays, zeolites, silica, alumina, or other matrices [18]. In recent years, β-zeolite [19], montmorillonite clays [20], SiO 2 , and Al 2 O 3 were employed as catalysts for this purpose to obtain relatively better results.…”
Section: Introductionmentioning
confidence: 99%